Forms of Pronouns - Saydaliyeva Dilfuza (Genius Journals, 2022)
Pronouns are the words that express these concepts. Thus, a circle of basic pronominal meanings emerges. These meanings are closely related to the concept of a person and must find their expression in the language.
Keywords: Indefinite; personal; possessive and reflexive pronouns